Optimizing the Role of the South Sulawesi Inspectorate in Handling Regional Government Supervision Issues to Achieve Transparency and Accountability - Tenri Liweng, Andi Darmawansya; Iqbal N, Muh. Nur; Akram, Khairil (Golden Ratio of Law and Social Policy Review, 2024)
This research aims to gain understanding and offer solutions regarding the supervision of the South Sulawesi Provincial Inspectorate in the implementation of regional government. Apart from that, this research also aims to identify factors that influence the essence of Inspectorate supervision in regional government and understand the function of the South Sulawesi Provincial Inspectorate. This type of research uses a combined approach between normative legal research or doctrinal legal research (normative legal research) and empirical legal research or non-doctrinal legal research (socio-legal research). The research results show that the supervision of the South Sulawesi Provincial Inspectorate has not been optimal in the administration of regional government. Factors that influence Inspectorate supervision include institutions, budget and human resources. The Inspectorate's supervisory function through attribution, delegation and mandate has a strong basis, but it is necessary to strengthen regulations which are expected to have an impact on the supervision and evaluation mechanism of the South Sulawesi Provincial Inspectorate. And the recommendation in this research is to strengthen the accountability line of defense in coaching and supervision according to the three lines of defense concept, by optimizing risk management and internal control in regional apparatus organizations. Strengthening regulations to support the institutional independence of the Inspectorate, increasing supervisory budget allocations, as well as a system for recruiting competent, high integrity and professional auditors and strengthening regulations related to the function of the South Sulawesi Provincial Inspectorate and changes from the old paradigm to the new paradigm.